Low back pain some real answers - Sweetman, Brian J. (Tfm Pub., 2005)
Back pain is the commonest form of rheumatism and it is estimated to affect between 65 to 80 per cent of populations sampled. The actual symptom of back pain is one of the commonest and most perplexing encountered in medical practice. A proper understanding of what it means is crucial for further medical advance. This book deals with this topic.